2017
DOI: 10.1515/ract-2016-2714
|View full text |Cite
|
Sign up to set email alerts
|

Radiocomplexation and bioevaluation of 99mTc nitrido-piracetam as a model for brain imaging

Abstract: AbstractThe aim of the work is to radiolabel a piracetam using [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…It was shown to be stable in saline for up to 48 hours. By contrast, in serum after 12 hours, the purity dropped to 97.0% and decreased to 85% at 48 hours …”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…It was shown to be stable in saline for up to 48 hours. By contrast, in serum after 12 hours, the purity dropped to 97.0% and decreased to 85% at 48 hours …”
Section: Resultsmentioning
confidence: 87%
“…This indicated that the tracer is excreted through urinary pathways. After 30 minutes, the [ 125 I]iodorolipram uptake notably decreased in the blood, bone, spleen, brain, stomach, muscle, heart, lungs, and liver . The uptake of [ 125 I]iodorolipram in brain is 7.6% ID/g at 10 minutes p.i.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…scarification of animals was conducted after certain times (5 min, 15 min, 30 min, 60 min and 2 h) after injection. Organs were collected in addition to (Fresh blood, bone, and muscle tissues) then measured against prepared standard solution of the labeled substrate [ [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] ]. The mean percentage of the injected dose was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…At time intervals, the stability of [ 125/131 I]iodobalsalazide radiotracer in two different media was assayed using TLC or HPLC techniques and counted in a well-type γ-scintillation counter. [71][72][73][74][75]…”
Section: Stability In Two Different Mediamentioning
confidence: 99%